Preparation method of catalyst for electrode

By treating the nickel-based alloy substrate with an acid corrosion solution and combining ultrasonic treatment, a one-step preparation of NiFe powder catalyst and NiFe self-supporting catalyst was achieved, solving the problem of high manufacturing costs in the prior art, and achieving efficient and low-cost catalyst preparation.

CN119753729APending Publication Date: 2025-04-04HUANENG YIMIN COAL POWER CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411863617.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, NiFe powder catalyst and NiFe self-support catalyst are synthesized through different process routes, resulting in higher manufacturing costs.

Method used

The acid corrosion solution is obtained by mixing the raw materials of fluoride, trivalent ferrous ion salt and buffer solution. The acid corrosion solution is used to corrode the nickel-based alloy substrate, combined with ultrasonic treatment and drying, and one-step preparation of NiFe powder catalyst and NiFe self-supporting catalyst is achieved.

Benefits of technology

The NiFe powder catalyst and NiFe self-supporting catalyst are achieved at the same time under room temperature. Both show excellent water oxidation properties in the alkaline electrolyte solution, reducing manufacturing costs, and providing useful reference for the industrial preparation of Ni-based anode catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753729A_ABST
    Figure CN119753729A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a catalyst for an electrode. The preparation method comprises the following steps: S1, mixing raw materials including fluoride, ferric ion salt and a buffer solution to obtain an acidic corrosive liquid; s2, the nickel-based alloy base material is sequentially subjected to cleaning and first drying, and the treated nickel-based alloy base material is obtained; s3, the treated nickel-based alloy base material is subjected to corrosion treatment with an acidic corrosion solution and then subjected to ultrasonic treatment, separation and secondary drying in sequence, a catalyst for the electrode is obtained, and the catalyst for the electrode comprises a NiFe powder catalyst and a NiFe self-supporting catalyst; wherein the pH value of the buffer solution is 6-8. According to the preparation method disclosed by the invention, the NiFe powder catalyst and the NiFe self-supporting catalyst are simultaneously prepared in one step, so that the utilization rate of precursor salt is improved, and the cost is remarkably saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a method for preparing a catalyst for an electrode. Background Art

[0002] The consumption of chemical energy plays a pivotal role in the development of human industrial society, but the environmental pollution and energy crisis brought about by it have also caused serious damage to the social economy. Therefore, the preparation of environmentally friendly hydrogen energy through renewable energy such as wind energy and solar energy has become an important way to solve the above dilemma. Among the many water electrolysis hydrogen production technologies, solid electrolyte water electrolysis hydrogen production has the advantages of high energy density, strong dynamic response characteristics, and pressure difference operation. PEM and AEM water electrolysis are two common configurations, in which electrodes are the core components of both, accounting for about 40% of the total manufacturing cost. Compared with PEM, the anode side catalyst of AEM can use nickel-iron-based catalysts that are thermodynamically stable and have excellent performance under alkaline conditions instead of precious metal Ir or Ru-based catalysts. Common AEM water electrolysis catalysts are mainly divided into powder catalysts and self-supporting catalysts, which are used for membrane electrode preparation with CCM and CCS as manufacturing processes respectively. In the common catalyst preparation method, high-performance powders and self-supporting catalysts are synthesized by different process routes, and cannot be prepared simultaneously by a one-step method, which invisibly increases the manufacturing cost of the finished catalyst. Summary of the invention

[0003] The main purpose of the present invention is to provide a method for preparing an electrode catalyst to solve the problem in the prior art that NiFe powder catalysts and NiFe self-supporting catalysts have to be synthesized through different process routes, resulting in high manufacturing costs.

[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a method for preparing an electrode catalyst, the preparation method comprising: step S1, mixing raw materials including fluoride, trivalent iron ion salt and buffer solution to obtain an acidic corrosive solution; step S2, sequentially cleaning and first drying a nickel-based alloy substrate to obtain a treated nickel-based alloy substrate; step S3, corroding the treated nickel-based alloy substrate with the acidic corrosive solution, then sequentially performing ultrasonic treatment, separation and second drying to obtain an electrode catalyst, the electrode catalyst comprising a NiFe powder catalyst and a NiFe self-supporting catalyst; wherein the pH value of the buffer solution is 6 to 8.

[0005] Furthermore, in the above step S1, the fluoride is selected from any one or more of ammonium fluoride, sodium fluoride and potassium fluoride; and / or, step S1 comprises: mixing a buffer solution with a fluoride to obtain a weak alkaline solution; mixing the weak alkaline solution with a solution of a trivalent iron ion salt to obtain an acidic corrosive solution; wherein, in terms of fluoride ions, the concentration of the fluoride in the weak alkaline solution is 0.001 to 1 mol / L.

[0006] Furthermore, in the above step S1, the ferric ion salt is ferric chloride and / or ferric nitrate; and / or, in terms of iron ions, the concentration of the ferric ion salt in the acidic etching solution is 0.01 to 1 mol / L; and / or, the pH value of the acidic etching solution is 2 to 4.

[0007] Furthermore, in the above step S1, the buffer solution is a mixed solution of boric acid and sodium hydroxide, in which the concentration of boric acid is 0.01 to 10 mol / L, and the concentration of sodium hydroxide is 0.01 to 10 mol / L.

[0008] Further, in the above step S2, the nickel-based alloy substrate is a nickel mesh containing an alloy coating and / or a nickel-based foam metal that has been densified; and / or the nickel-based foam metal is selected from any one or more of foam nickel, foam nickel-cobalt and foam nickel-iron; and / or the surface of the nickel mesh containing an alloy coating includes an alloy coating, and the alloy coating is synthesized by thermal spraying of metal powder with a particle size of 100 to 500 mesh, and / or the metal in the alloy coating includes aluminum and a transition metal, and the transition metal is selected from any one or more of iron, cobalt, nickel, copper, zinc, molybdenum and tungsten; and / or the thickness of the nickel-based alloy substrate is 0.1 to 1.0 mm; and / or the porosity of the nickel-based foam metal that has been densified is 20 to 50%; and / or the mesh form of the substrate of the nickel mesh containing an alloy coating is a woven mesh, a stretched mesh or a stamped mesh.

[0009] Furthermore, in the above step S2, the cleaning process includes sequentially washing the nickel-based alloy substrate with hydrochloric acid, water, acetone and ethanol; the preferred cleaning method is ultrasonic cleaning, and the total time of ultrasonic cleaning is 1 to 15 minutes; and / or the concentration of hydrochloric acid in the hydrochloric acid washing is 1 to 5 mol / L.

[0010] Furthermore, when the above-mentioned nickel-based alloy substrate is a nickel mesh containing an alloy coating, the preparation method also includes: a process of dealumination of the nickel mesh containing an alloy coating using an alkaline solution; wherein the alkaline solution is a mixture of a strong alkaline solution and / or a weak alkaline solution, the strong alkaline solution is a sodium hydroxide solution and / or a potassium hydroxide solution, and the mass concentration of the strong alkaline solution is 10 to 30%; and / or the weak alkaline solution is a sodium potassium tartrate solution, and the mass concentration of the weak alkaline solution is 1 to 30%.

[0011] Furthermore, in the above step S3, the temperature of the corrosion treatment is 25 to 75° C., preferably the temperature of the corrosion treatment is 25 to 35° C.; and / or the time of the corrosion treatment is 1 to 240 min.

[0012] Furthermore, in the above step S3, the power of the ultrasonic treatment is 5 to 60 W, and the time of the ultrasonic treatment is 1 to 15 min.

[0013] Furthermore, in the above step S3, the second drying method is selected from any one or more of air drying, vacuum drying and freeze drying.

[0014] Applying the technical scheme of the present invention, when trivalent iron ions are in a weakly acidic corrosive solution, the nickel-based alloy substrate reacts with the hydrogen ions in the acidic corrosive solution and gradually dissolves in the acidic corrosive solution to form Ni ions, so that the pH value in the reaction system rises until it is neutral, thereby converting the soluble Ni ions in the reaction system into nickel-based hydroxide precipitated powders, and the surface of the nickel-based alloy substrate also generates nickel-based hydroxides in situ at the same time, thereby preparing NiFe powder catalysts and NiFe self-supporting catalysts at the same time under room temperature conditions in the next step, both of which show excellent water oxidation performance in alkaline electrolyte solutions, and can be used as efficient anode materials for alkaline water electrolysis and AEM electrolysis of water. The preparation process of the present application does not involve high-temperature calcination and high-pressure hydrothermal processes, has the advantages of simple process, low cost of raw materials, and short preparation cycle, and can achieve proportionally enlarged macro-scale preparation, which provides a useful reference for the industrial preparation of Ni-based anode catalysts. Compared with the traditional foam metal electrode prepared by corrosion method, the present invention further utilizes the phenomenon of increased solution pH value during corrosion process while preparing the metal electrode, and simultaneously synthesizes the powder catalyst, thereby improving the utilization rate of the precursor salt and significantly saving costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0016] Figure 1 The NiFe powder catalyst and the NiFe self-supporting catalyst in Example 1 of the present application are shown, wherein: Figure 1 a represents NiFe self-supporting catalyst, Figure 1 b represents the solution and precipitation after the corrosion reaction of the nickel-based alloy substrate. Figure 1 c represents the NiFe powder catalyst obtained after precipitation, filtration and drying.

[0017] Figure 2 The NiFe powder catalyst in Example 1 of the present application and the commercial IrO 2(a) Catalytic performance of alkaline oxygen evolution reaction measured by linear voltammetry in a three-electrode system, and (b) EIS graph measured by electrochemical impedance spectroscopy.

[0018] Figure 3 The NiFe self-supporting catalyst in Example 1 of the present application and the commercial IrO 2 (a) Catalytic performance of alkaline oxygen evolution reaction measured by linear voltammetry in a three-electrode system, and (b) EIS graph measured by electrochemical impedance spectroscopy.

[0019] Figure 4 The membrane electrode assembly prepared by using NiFe powder catalyst as the membrane electrode anode catalyst and NiFe self-supporting catalyst as the anode gas diffusion layer in Example 1 of the present application is shown in FIG. 2 Performance diagram applied to an AEM electrolysis cell. DETAILED DESCRIPTION

[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0021] As analyzed in the background technology of this application, in the prior art, NiFe powder catalysts and NiFe self-supporting catalysts have to be synthesized through different process routes, resulting in high manufacturing costs. In order to solve the above problem, this application provides a method for preparing electrode catalysts.

[0022] In a typical embodiment of the present application, a method for preparing an electrode catalyst is provided, the preparation method comprising: step S1, mixing raw materials including fluoride, trivalent iron ion salt and buffer solution to obtain an acidic corrosive solution; step S2, sequentially cleaning and first drying a nickel-based alloy substrate to obtain a treated nickel-based alloy substrate; step S3, corroding the treated nickel-based alloy substrate with an acidic corrosive solution, then sequentially performing ultrasonic treatment, separation and second drying to obtain an electrode catalyst, the electrode catalyst comprising a NiFe powder catalyst and a NiFe self-supporting catalyst; wherein the pH value of the buffer solution is 6 to 8.

[0023] In the weakly acidic corrosive solution of trivalent iron ions, the nickel-based alloy substrate reacts with the hydrogen ions in the acidic corrosive solution and gradually dissolves in the acidic corrosive solution to form Ni ions, so that the pH value in the reaction system rises until it is neutral, thereby converting the soluble Ni ions in the reaction system into nickel-based hydroxide precipitated powders, and the surface of the nickel-based alloy substrate also generates nickel-based hydroxides in situ at the same time, so that the NiFe powder catalyst and the NiFe self-supporting catalyst are prepared at room temperature in the next step, both of which show excellent water oxidation performance in alkaline electrolyte solutions, and can be used as efficient anode materials for alkaline water electrolysis and AEM electrolysis of water. The preparation process of the present application does not involve the process of high-temperature calcination and high-pressure hydrothermal, has the advantages of simple process, low cost of raw materials, and short preparation cycle, and can achieve macro-scale preparation of equal proportions, which provides a useful reference for the industrial preparation of Ni-based anode catalysts. Compared with the traditional foam metal electrode prepared by the corrosion method, the present invention, while preparing the metal electrode, further utilizes the phenomenon that the pH value of the solution increases during the corrosion process, and synthesizes the powder catalyst synchronously, thereby improving the utilization rate of the precursor salt and significantly saving costs.

[0024] The NiFe self-supporting catalyst obtained by the above preparation method is used as the anode gas diffusion layer of the AEM electrolytic cell, and the NiFe powder catalyst is loaded on the commercial cathode exchange membrane through the CCM process as the anode catalyst, thereby integrating the two forms of catalyst into the water splitting device at the same time to jointly solve the problems of slow OER kinetics and high overpotential.

[0025] In one embodiment of the present application, in the above step S1, the fluoride is selected from any one or more of ammonium fluoride, sodium fluoride and potassium fluoride; and / or, step S1 includes: mixing a buffer solution with a fluoride to obtain a weak alkaline solution; mixing the weak alkaline solution with a solution of a trivalent iron ion salt to obtain an acidic corrosive solution; wherein, in terms of fluoride ions, the concentration of fluoride in the weak alkaline solution is 0.001 to 1 mol / L.

[0026] The addition of fluoride can promote the dissolution of metal ions in the etching solution and the growth of the catalyst. The control of its concentration affects the corrosion rate and the morphology of the catalyst. By controlling the type and concentration range of fluoride, it is beneficial to improve the performance of the etching solution, thereby improving the activity and stability of the catalyst. By first mixing the buffer solution with fluoride and then adding trivalent iron ion salt, it is beneficial to finely adjust the chemical environment of the etching solution, thereby controlling the synthesis of NiFe-based catalysts.

[0027] In one embodiment of the present application, in the above step S1, the trivalent iron ion salt is ferric chloride and / or ferric nitrate; and / or, in terms of iron ions, the concentration of the trivalent iron ion salt in the acidic etching solution is 0.01 to 1 mol / L; and / or, the pH value of the acidic etching solution is 2 to 4.

[0028] The concentration of trivalent iron ion salt in the acidic corrosive solution directly affects the depth and rate of the corrosion process. The pH value of the acidic corrosive solution affects the dissolution and precipitation of metal corrosion products. The appropriate pH value and concentration of trivalent iron ions can promote the reaction between Fe ions and the nickel-based alloy substrate to generate a NiFe-based catalyst with a layered double hydroxide structure, thereby ensuring the formation of NiFe-based self-supporting catalysts and promoting the synthesis of NiFe-based powder catalysts. At the same time, it also reduces the damage to the substrate caused by the excessive acidity of the corrosive solution, and balances the rate of the chemical reaction and the strength of the nickel-based alloy substrate structure.

[0029] In one embodiment of the present application, in the above step S1, the buffer solution is a mixed solution of boric acid and sodium hydroxide, in which the concentration of boric acid is 0.01 to 10 mol / L, and the concentration of sodium hydroxide is 0.01 to 10 mol / L.

[0030] The appropriate pH value can promote the dissolution of metal ions and the growth of catalysts, reduce the adverse effects of too high or too low pH on the reaction, and improve the morphology and activity of the catalyst. The mixed solution of boric acid and sodium hydroxide is used as a buffer solution. By controlling the concentration of boric acid and sodium hydroxide within the above range, it helps to reduce Fe 3+ The risk of rapid pH fluctuations due to corrosion of the nickel-based alloy substrate is great, and relatively slow pH changes are crucial for the simultaneous synthesis of NiFe powder catalysts and NiFe self-supporting catalysts.

[0031] In one embodiment of the present application, in the above step S2, the nickel-based alloy substrate is a nickel mesh containing an alloy coating and / or a nickel-based foam metal that has been densified; and / or the nickel-based foam metal is selected from any one or more of foam nickel, foam nickel-cobalt and foam nickel-iron; and / or the surface of the nickel mesh containing an alloy coating includes an alloy coating, and the alloy coating is synthesized by thermal spraying of metal powder with a particle size of 100 to 500 mesh, and / or the metal in the alloy coating includes aluminum and a transition metal, and the transition metal is selected from any one or more of iron, cobalt, nickel, copper, zinc, molybdenum and tungsten; and / or the thickness of the nickel-based alloy substrate is 0.1 to 1.0 mm; and / or the porosity of the nickel-based foam metal that has been densified is 20 to 50%; and / or the mesh form of the substrate of the nickel mesh containing an alloy coating is a woven mesh, a stretched mesh or a stamped mesh.

[0032] The choice of nickel-based alloy substrate affects the distribution and diffusion path of the catalyst. By controlling the thickness and porosity of the nickel-based alloy substrate, the electron transport and gas diffusion of the obtained catalyst can be optimized, and the loading amount and catalytic efficiency of the catalyst can be increased. The advantage of nickel-based foam metal is that it is simple and convenient to obtain, but the types of alloy elements are relatively small. The advantage of nickel mesh containing alloy coating is that it has high strength and a large variety of alloy elements that can be melted on the surface, which can enrich the types of catalysts and enhance their strength. However, nickel mesh containing alloy coating often needs to be obtained through pre-treatment, such as thermal spraying to form an alloy coating on the surface of the nickel-based mesh metal, and using an alkaline solution to dealuminate the alloy coating to obtain a nickel-based mesh alloy that meets the requirements.

[0033] In one embodiment of the present application, in the above step S2, the cleaning process includes sequentially washing the nickel-based alloy substrate with hydrochloric acid, water, acetone and ethanol; the preferred cleaning method is ultrasonic cleaning, and the total time of ultrasonic cleaning is 1 to 15 minutes; and / or, the concentration of hydrochloric acid in the hydrochloric acid washing is 1 to 5 mol / L.

[0034] The above cleaning process is conducive to removing the oxide layer and impurities on the surface of the nickel-based alloy substrate, thereby reducing the adverse effects of surface impurities on corrosion and catalyst growth processes, and improving the performance and yield rate of the catalyst. Ultrasonic cleaning is preferred and the total time of ultrasonic cleaning is controlled, which is conducive to improving the cleaning efficiency and the purity of the surface of the nickel-based alloy substrate. By controlling the concentration of hydrochloric acid within the above range, it is conducive to balancing the cleaning effect and the degree of corrosion of the nickel-based alloy substrate, reducing the risk of damage to the nickel-based alloy substrate due to excessive cleaning.

[0035] In one embodiment of the present application, when the nickel-based alloy substrate is a nickel mesh containing an alloy coating, the above-mentioned preparation method also includes: a process of dealumination of the nickel mesh containing the alloy coating using an alkaline solution; wherein the alkaline solution is a mixture of a strong alkaline solution and / or a weak alkaline solution, and / or the strong alkaline solution is a sodium hydroxide solution and / or a potassium hydroxide solution, and the mass concentration of the strong alkaline solution is 10 to 30%; and / or the weak alkaline solution is a sodium potassium tartrate solution, and the mass concentration of the weak alkaline solution is 1 to 30%.

[0036] Sodium hydroxide or potassium hydroxide solution, as a strong alkaline solution, accelerates the dissolution of Al in the alloy coating on the surface of the nickel mesh containing the alloy coating, while the addition of sodium potassium tartrate solution slows down the corrosion of the alloy coating. By controlling the mass concentration of the strong alkaline solution and the weak alkaline solution in the dealumination process within the above range, it is beneficial to efficiently remove the aluminum component in the alloy coating, and the porous structure constructed on the surface of the nickel mesh containing the alloy coating can promote the Fe 3+ The corrosion reaction is carried out, which helps to synthesize the NiFe self-supporting catalyst with high specific surface area and improves the generation rate of NiFe powder catalyst.

[0037] In one embodiment of the present application, in the above step S3, the temperature of the corrosion treatment is 25-75° C., preferably the temperature of the corrosion treatment is 25-35° C.; and / or the time of the corrosion treatment is 1-240 min.

[0038] The appropriate corrosion temperature can accelerate the dissolution of metal ions and the formation of layered double hydroxides, while the control of time is conducive to the full progress of the catalyst growth process and reduces the risk of excessive corrosion. By controlling the temperature and time of the corrosion treatment within the above range, it is conducive to improving the controllability of the catalyst growth process, reducing the risk of catalyst structure damage caused by overheating or long reaction time, thereby improving the activity and stability of the catalyst and reducing energy consumption in the production process.

[0039] In one embodiment of the present application, in the above step S3, the power of the ultrasonic treatment is 5 to 60 W, and the time of the ultrasonic treatment is 1 to 15 min.

[0040] It is preferred to control the power and time of the ultrasonic treatment within the above range, which is beneficial to more fully separate the NiFe self-supporting catalyst from the NiFe powder catalyst, and is also beneficial to remove physically adsorbed impurities and residual corrosive liquid on the surface of the catalyst, thereby improving the purity and activity of the catalyst, simplifying the post-treatment process, and reducing production costs.

[0041] In one embodiment of the present application, in the above step S3, the second drying method is selected from any one or more of forced air drying, vacuum drying and freeze drying.

[0042] Different drying methods have a significant impact on the structure and properties of the catalyst. By controlling the second drying method, it is beneficial to improve the drying efficiency and uniformity of the catalyst, reduce catalyst agglomeration during the drying process, and improve the dispersion of the catalyst and its activity in subsequent applications.

[0043] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0044] Example 1

[0045] 1) Prepare 100 mL of a buffer solution consisting of 0.1 mmol / L boric acid and 0.01 mmol / L sodium hydroxide, and adjust the pH value of the buffer solution to about 7;

[0046] 2) Add 5 mmol of sodium fluoride to the above buffer solution to obtain a weak alkaline solution, the concentration of fluoride in the weak alkaline solution is 0.05 mol / L, and after ultrasonic dissolution, add 10 mmol of ferric nitrate nonahydrate to obtain an acidic etching solution, the concentration of trivalent iron ion salt in the acidic etching solution is 0.1 mol / L, and the pH value of the acidic etching solution is 3;

[0047] 3) The nickel foam with a thickness of 3 mm was washed with 3 mol / L hydrochloric acid solution, ultrapure water, ethanol, acetone and water in sequence, and then dried. After drying, it was compressed to a thickness of 0.3 mm by a hot press to obtain a nickel foam with a porosity of 35%;

[0048] 4) Immerse the foamed nickel with a porosity of 35% in the acidic etching solution in step 2, control the temperature at 25° C., and perform the etching treatment for 120 minutes while the solution is stirred;

[0049] 5) The electrode and the corrosive solution were ultrasonically treated at a power of 25 W and a time of 5 min to separate the NiFe supported catalyst from the NiFe powder catalyst. The nickel foam was then taken out, rinsed with water and placed in a constant temperature drying oven for drying. The obtained sample was a NiFe self-supporting catalyst (such as Figure 1 a); while separating the orange-yellow NiFe precipitate in the solution by centrifugation (as Figure 1 b), and freeze-drying is used to remove the remaining water, and the resulting powder is a NiFe powder catalyst (as shown in Figure 1 c).

[0050] Example 2

[0051] The synthesis of NiFe powder and self-supporting catalyst on metal mesh substrate is as follows:

[0052] Prepare 100 mL of a buffer solution consisting of 0.1 mmol / L boric acid and 0.01 mmol / L sodium hydroxide, with a pH of about 7;

[0053] Add 5 mmol of sodium fluoride to the above buffer solution to obtain a weak alkaline solution, the concentration of fluoride in the weak alkaline solution is 0.05 mol / L, add 10 mmol of ferric nitrate nonahydrate after ultrasonic dissolution to obtain an acidic etching solution, the concentration of trivalent iron ion salt in the acidic etching solution is 0.1 mol / L, and the pH value of the acidic etching solution is 3;

[0054] By plasma thermal spraying, an alloy powder composed of nickel and aluminum (the powder form is aluminum-coated nickel, the composition is 80% nickel and 20% aluminum, and the particle size is 150 mesh to 325 mesh) is sprayed on a 46-mesh woven nickel mesh, and then placed in 30% sodium hydroxide and 10% sodium potassium tartrate for dealloying activation, and then washed with deionized water to neutrality.

[0055] Immerse all the above electrodes in the acidic etching solution in step 2, control the temperature at 25°C, and perform etching treatment for 4 hours while the solution is stirred;

[0056] The electrode and the corrosive solution were ultrasonically treated to separate the NiFe self-supporting catalyst and the NiFe powder catalyst. The nickel foam was then taken out, rinsed with water and placed in a constant temperature drying oven for drying. The obtained samples were the NiFe self-supporting catalyst and the NiFe powder catalyst.

[0057] Example 3

[0058] The difference from Example 1 is that the concentration of fluoride in the weak alkaline solution is 0.001 mol / L, and the samples finally obtained are NiFe self-supporting catalysts and NiFe powder catalysts.

[0059] Example 4

[0060] The difference from Example 1 is that the concentration of fluoride in the weak alkaline solution is 1 mol / L, and finally a NiFe self-supporting catalyst and a NiFe powder catalyst are obtained.

[0061] Example 5

[0062] The difference from Example 1 is that the concentration of fluoride in the weak alkaline solution is 0.0005 mol / L, and finally a NiFe self-supporting catalyst and a NiFe powder catalyst are obtained.

[0063] Example 6

[0064] The difference from Example 1 is that the concentration of the trivalent iron ion salt in the acidic etching solution is 0.01 mol / L, the pH value of the acidic etching solution is 4, and finally a NiFe self-supporting catalyst and a NiFe powder catalyst are obtained.

[0065] Example 7

[0066] The difference from Example 1 is that the concentration of the trivalent iron ion salt in the acidic etching solution is 1 mol / L, the pH value of the acidic etching solution is 2, and finally a NiFe self-supporting catalyst and a NiFe powder catalyst are obtained.

[0067] Example 8

[0068] The difference from Example 1 is that the concentration of the trivalent iron ion salt in the acidic etching solution is 0.005 mol / L, the pH value of the acidic etching solution is 5, and finally a NiFe self-supporting catalyst and a NiFe powder catalyst are obtained.

[0069] Example 9

[0070] The difference from Example 1 is that the porosity of the nickel foam is 20%, and finally a NiFe self-supporting catalyst and a NiFe powder catalyst are obtained.

[0071] Example 10

[0072] The difference from Example 1 is that the porosity of the nickel foam is 90%, and finally a NiFe self-supporting catalyst and a NiFe powder catalyst are obtained.

[0073] Embodiment 11

[0074] The difference from Example 2 is that the pressed nickel foam is placed in sodium hydroxide with a mass concentration of 40% and sodium potassium tartrate with a mass concentration of 1% for dealloying activation, and finally a NiFe self-supporting catalyst and a NiFe powder catalyst are obtained.

[0075] Example 12

[0076] The difference from Example 1 is that the temperature of the corrosion treatment is 75° C., and the corrosion treatment is carried out for 240 min while the solution is in a stirring state; finally, a NiFe self-supporting catalyst and a NiFe powder catalyst are obtained.

[0077] Example 13

[0078] The difference from Example 1 is that the power of ultrasonic treatment is 75 W and the time of ultrasonic treatment is 30 min; finally, NiFe self-supporting catalyst and NiFe powder catalyst are obtained.

[0079] Embodiment 14

[0080] The difference from Example 2 is that the plasma spraying in step 3) is changed to supersonic flame spraying, the powder particle size is changed to 325-500 mesh, and the other steps are the same.

[0081] Embodiment 15

[0082] The difference from Example 2 is that the plasma spraying in step 3) is changed to supersonic arc spraying, the powder is changed to alloy wire, and the other steps are the same.

[0083] Performance Testing:

[0084] Test example of using NiFe powder catalyst alone

[0085] The NiFe powder catalysts obtained in the above examples were used for oxygen evolution reaction in alkaline electrolyte. In a three-electrode test system, a platinum wire was used as a counter electrode, a mercury / mercuric oxide electrode was used as a reference electrode, and 1 mol / L potassium hydroxide was selected as the electrolyte in the test system.

[0086] 100 μL NiFe powder catalyst dispersion was added to 4 mL of water and isopropanol mixed solvent, and a uniform catalyst ink was formed after ultrasonic treatment. Then a certain amount of ink was evenly dropped on a 5 mm glassy carbon rotating disk electrode as a working electrode for testing. The loading was 0.255 mg / cm 2 , the disc speed in the test was 2500rpm.

[0087] The electrochemical data were tested by linear voltammetry and electrochemical impedance spectroscopy. The linear voltammetry scan rate was 5 mV / s and the test electrode was tested at 10 mA / cm 2 The lower the overpotential of hydrogen evolution under the current density, the better the catalytic performance; the test potential of AC impedance is 1.53V (vs.RHE), the AC amplitude is 10mV, and the frequency range is 10 6 ~10 -1 Hz, the charge transfer resistance is obtained by fitting the equivalent circuit of the impedance spectrum. The lower the value, the better the electron transfer performance.

[0088] Example 1 and commercial IrO 2 The test results are as follows Figure 2 As shown in a, NiFe powder catalyst is at 10mA / cm 2 The overpotential at the current density is 272 mV, which is better than the commercial noble metal catalyst IrO 2 330mV.

[0089] Example 1 and commercial IrO 2 The charge transfer resistance test results are as follows Figure 2 As shown in b, the charge transfer resistance of NiFe powder catalyst is lower than that of commercial IrO 2 The charge transfer resistance of the catalyst indicates that the charge transfer between the NiFe powder catalyst interface and the electrolyte is fast, showing its high oxygen evolution catalytic activity.

[0090] Test example of using NiFe self-supporting catalyst alone

[0091] The NiFe self-supporting catalyst obtained in the above examples was cut into a rectangular block with a length of 1.5 cm, a width of 1 cm, and a thickness of 0.3 mm, and fixed with an electrode clamp as a working electrode for oxygen evolution reaction in an alkaline electrolyte. In the three-electrode test system, the platinum wire is the counter electrode, the mercury / mercuric oxide electrode is the reference electrode, and the effective area of ​​the working electrode immersed in the electrolyte is 1 cm 2, the test system selected 1 mol / L potassium hydroxide as the electrolyte.

[0092] The electrochemical data were tested by linear voltammetry and electrochemical impedance spectroscopy: the linear voltammetry scan rate was 5 mV / s, and the test electrode was tested at 100 mA / cm 2 The lower the overpotential of hydrogen evolution under the current density, the better the catalytic performance; the test potential of AC impedance is 1.53V (vs.RHE), the AC amplitude is 10mV, and the frequency range is 10 6 ~10 -1 Hz, the charge transfer resistance is obtained by fitting the equivalent circuit of the impedance spectrum. The lower the value, the better the electron transfer performance.

[0093] Example 1 and commercial IrO 2 The test results are as follows Figure 3 As shown in a, the NiFe self-supporting catalyst is at 100 mA / cm 2 The overpotential at the current density is 259 mV, which is better than the commercial noble metal catalyst IrO 2 360mV.

[0094] Example 1 and commercial IrO 2 The charge transfer resistance test results are as follows Figure 3 b shows that the charge transfer resistance of the NiFe self-supporting catalyst is smaller than that of the commercial IrO 2 The charge transfer resistance of the electrode prepared by spraying on nickel foam indicates that the charge transfer between the NiFe self-supporting catalyst interface and the electrolyte is fast, showing its high oxygen evolution catalytic activity.

[0095] Test example of using NiFe powder catalyst and NiFe self-supporting catalyst together

[0096] The NiFe self-supporting catalyst obtained in the above example was ultrasonically sprayed onto a commercial AEM membrane electrode as an anode catalyst, and a commercial Pt / C catalyst was used as a cathode catalyst to prepare a CCM electrode.

[0097] (1) 225 mg of the NiFe powder catalyst obtained in the example was respectively prepared into a slurry with a total volume of 15 mL of water and isopropanol mixed for spraying, and an anion exchange membrane ionomer with a mass of 25% of the catalyst was added, and a uniform catalyst ink was formed after ultrasonic treatment;

[0098] (2) 225 mg of commercial Pt / C catalyst was prepared into a slurry with a total volume of 15 mL of water and isopropanol, and an anion exchange membrane ionomer with a mass of 20% of the catalyst was added, and a uniform catalyst ink was formed after ultrasonic treatment;

[0099] (3) Using ultrasonic spraying, the mixed spray slurry prepared in steps (1) and (2) was sprayed on both sides of the commercial AEM in sequence, with a loading of 2 mg / cm 2 ;

[0100] (4) The CCM membrane electrode prepared in step 3 was placed in a 1 mol / L NaOH solution and left to stand for activation for 24 hours before being used for subsequent single cell performance testing.

[0101] At the same time, the NiFe powder catalyst obtained in the example was used as a CCS electrode and directly used in the anode gas diffusion layer of the electrolytic cell, and the cathode diffusion layer was made of foamed nickel.

[0102] During the test, the electrode clamps of the electrochemical workstation were clamped on the positive and negative electrodes of the electrolytic cell, and 1M KOH solution was circulated at a flow rate of 100mL / min. The heating device was turned on and the temperature was set to 60℃. The samples reached 2A / cm in the electrolysis water test. 2 The chamber voltage at the current density represents the hydrogen production voltage value of a single electrolysis unit when a certain current density is reached. Therefore, the lower the value, the lower the energy consumption under the current density and the higher the economy of the hydrogen production reaction.

[0103] Example 1 and commercial IrO 2 The test results are as follows Figure 4 As shown in Figure 2, when NiFe self-supporting catalyst and NiFe powder catalyst are used together in AEM single cell, the electrolysis water test reaches 2A / cm 2 The cell voltage of the current density is only 1.98V, which is better than that of commercial IrO 2 The prepared membrane electrode has a voltage of 2.38V, which enables non-precious metal catalysts to effectively replace commercial precious metal catalysts.

[0104] Table 1

[0105]

[0106]

[0107] Examples 3, 4, and 5 show that the fluoride concentration in the solution affects the intensity of the electrode corrosion reaction, thereby changing the amount of catalytically active substances generated, microscopic morphology, degree of agglomeration, size, etc., and ultimately affecting the charge conduction performance of the catalyst;

[0108] Examples 6, 7, and 8 show that the concentration of ferric iron in the solution affects the depth and rate of the corrosion process, and that a proper concentration also helps the metal element components in the catalyst to be within the optimal ratio range;

[0109] Examples 9 and 10 show that the porosity of the foamed nickel substrate affects the controllability of the corrosion reaction, thereby affecting the amount, uniformity and structural integrity of the catalytically active substances generated;

[0110] Example 11 shows that the alloy coating on the electrode surface needs to undergo alloy dealumination reaction in an appropriate alkaline solution etching environment, which helps to reduce the risk of the alloy being oxidized to form surface oxides during this process, thereby reducing the risk of contamination by heteroatoms during the iron ion corrosion process;

[0111] Example 12 shows that the corrosion reaction temperature and time affect the formation process of layered oxides on the electrode surface, which in turn affects the catalyst composition and structure;

[0112] Example 13 shows that the ultrasonic power and time affect the separation effect and micromorphology of the self-supporting catalyst and the powder catalyst, and further affect the structural strength, purity and activity of the catalyst;

[0113] In Examples 14 and 15, supersonic flame spraying and supersonic arc spraying were used respectively to process the alloy coating on the surface of the nickel mesh, and the performance was similar to that of Example 2, which proved the versatility of the synthesis method of the present invention.

[0114] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0115] In the weakly acidic corrosive solution of trivalent iron ions, the nickel-based alloy substrate reacts with the hydrogen ions in the acidic corrosive solution and gradually dissolves in the acidic corrosive solution to form Ni ions, so that the pH value in the reaction system rises until it is neutral, thereby converting the soluble Ni ions in the reaction system into nickel-based hydroxide precipitated powders, and the surface of the nickel-based alloy substrate also generates nickel-based hydroxides in situ at the same time, so that the NiFe powder catalyst and the NiFe self-supporting catalyst are prepared at room temperature in the next step, both of which show excellent water oxidation performance in alkaline electrolyte solutions, and can be used as efficient anode materials for alkaline water electrolysis and AEM electrolysis of water. The preparation process of the present application does not involve the process of high-temperature calcination and high-pressure hydrothermal, has the advantages of simple process, low cost of raw materials, and short preparation cycle, and can achieve macro-scale preparation of equal proportions, which provides a useful reference for the industrial preparation of Ni-based anode catalysts. Compared with the traditional foam metal electrode prepared by the corrosion method, the present invention, while preparing the metal electrode, further utilizes the phenomenon that the pH value of the solution increases during the corrosion process, and synthesizes the powder catalyst synchronously, thereby improving the utilization rate of the precursor salt and significantly saving costs.

[0116] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an electrode catalyst, characterized in that: The preparation method comprises: Step S1, mixing raw materials including fluoride, trivalent iron ion salt and buffer solution to obtain an acidic etching solution; Step S2, sequentially cleaning and first drying the nickel-based alloy substrate to obtain a treated nickel-based alloy substrate; Step S3, using the acidic corrosive solution to corrode the treated nickel-based alloy substrate, and then sequentially performing ultrasonic treatment, separation, and second drying to obtain an electrode catalyst, wherein the electrode catalyst includes a NiFe powder catalyst and a NiFe self-supporting catalyst; Wherein, the pH value of the buffer solution is 6-8.

2. The preparation method according to claim 1, characterized in that: In step S1, the fluoride is selected from any one or more of ammonium fluoride, sodium fluoride and potassium fluoride; And / or, step S1 comprises: mixing the buffer solution with the fluoride to obtain a weak alkaline solution; Mixing the weak alkaline solution with a solution of a trivalent iron ion salt to obtain the acidic corrosive solution; Wherein, the concentration of the fluoride in the weak alkaline solution is 0.001-1 mol / L in terms of fluoride ions.

3. The preparation method according to claim 1 or 2, characterized in that: In step S1, the ferric iron salt is ferric chloride and / or ferric nitrate; and / or, in terms of iron ions, the concentration of the ferric iron salt in the acidic etching solution is 0.01 to 1 mol / L; and / or, the pH value of the acidic etching solution is 2 to 4.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step S1, the buffer solution is a mixed solution of boric acid and sodium hydroxide, in which the concentration of boric acid is 0.01 to 10 mol / L, and the concentration of sodium hydroxide is 0.01 to 10 mol / L.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step S2, the nickel-based alloy substrate is a nickel mesh containing an alloy coating and / or a nickel-based foam metal that has been densified; and / or the nickel-based foam metal is selected from any one or more of foam nickel, foam nickel-cobalt and foam nickel-iron; and / or the surface of the nickel mesh containing an alloy coating includes an alloy coating, and the alloy coating is synthesized by thermal spraying a metal powder with a particle size of 100 to 500 meshes, and / or the metal in the alloy coating includes aluminum and a transition metal, and the transition metal is selected from any one or more of iron, cobalt, nickel, copper, zinc, molybdenum and tungsten; And / or, the thickness of the nickel-based alloy substrate is 0.1 to 1.0 mm; And / or, the porosity of the densified nickel-based foam metal is 20-50%; And / or, the base mesh form of the nickel mesh containing the alloy coating is a woven mesh, a stretched mesh or a punched mesh.

6. The preparation method according to any one of claims 1 to 5, characterized in that In step S2, the cleaning process includes sequentially washing the nickel-based alloy substrate with hydrochloric acid, water, acetone and ethanol; preferably, the cleaning method is ultrasonic cleaning, and the total time of the ultrasonic cleaning is 1 to 15 minutes; And / or, the concentration of hydrochloric acid in the hydrochloric acid washing is 1 to 5 mol / L.

7. The preparation method according to claim 5, characterized in that: When the nickel-based alloy substrate is the nickel mesh containing the alloy coating, the preparation method further comprises: The process of dealuminating the nickel mesh containing the alloy coating by using an alkaline solution; Wherein, the alkaline solution is a mixture of a strong alkaline solution and / or a weak alkaline solution, the strong alkaline solution is a sodium hydroxide solution and / or a potassium hydroxide solution, and the mass concentration of the strong alkaline solution is 10-30%; and / or the weak alkaline solution is a sodium potassium tartrate solution, and the mass concentration of the weak alkaline solution is 1-30%.

8. The preparation method according to any one of claims 1 to 7, characterized in that In the step S3, the temperature of the corrosion treatment is 25 to 75° C., preferably the temperature of the corrosion treatment is 25 to 35° C.; and / or the time of the corrosion treatment is 1 to 240 minutes.

9. The preparation method according to any one of claims 1 to 8, characterized in that: In the step S3, the power of the ultrasonic treatment is 5 to 60 W, and the time of the ultrasonic treatment is 1 to 15 minutes.

10. The preparation method according to any one of claims 1 to 9, characterized in that: In step S3, the second drying method is selected from any one or more of air drying, vacuum drying and freeze drying.

Citation Information

Cited By

  • Preparation method of noble metal atom anchored hydroxide-based oxygen evolution electrode

    CN121137647A